2019
DOI: 10.3390/ijerph16244889
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of Neighbourhood, School, Friend and Individual-Level Variation in Primary School Children’s Physical Activity

Abstract: Physical activity is influenced by individual, inter-personal and environmental factors. In this paper, we explore the variability in children’s moderate-to-vigorous physical activity (MVPA) at different individual, parent, friend, school and neighbourhood levels. Valid accelerometer data were collected for 1077 children aged 9, and 1129 at age 11, and the average minutes of MVPA were derived for weekdays and weekends. We used a multiple-membership, multiple-classification model (MMMC) multilevel model to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This situation can contribute to females not participating in team sports activities because they feel they will not be successful [ 52 ]. In relation to males, greater participation in sports activities contributes to promoting social relationships [ 53 ] as well as an improvement in physical well-being produced by the benefits of PA on health [ 54 ]. However, it is important to analyze these associations with larger samples to verify the differences in the associations between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…This situation can contribute to females not participating in team sports activities because they feel they will not be successful [ 52 ]. In relation to males, greater participation in sports activities contributes to promoting social relationships [ 53 ] as well as an improvement in physical well-being produced by the benefits of PA on health [ 54 ]. However, it is important to analyze these associations with larger samples to verify the differences in the associations between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that friends play an important role in physical activity, with similar activity levels between children and their close friends, and evidence that friends influence each other's physical activity among adolescents [62][63][64]. In addition, the importance of friendship networks increases as children age, with around 20% of the variability in MVPA attributable to friendship networks for girls at age 11 [65]. Thus, there may be mediating effects at school and/or network level as well as at an individual level.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of social influences in physical among children has been well documented in pre-pandemic research [ 30 , 32 , 33 ]. Loss of social connections among children during periods of lockdown and isolation and its impact on wellbeing and physical activity has emerged in recent qualitative research [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%